My mom's the best - Smith, Rosie 1956-; Whatley, Bruce (New York : Sterling Children's Books, 2017)
Animals describe the reasons their mom is special, including giving hugs, taking them to school, teaching them to dance, and making bathtime fun.
Cover title.
106101
Keywords: Board books; Mother and child -- Fiction; Animals -- Juvenile Fiction; Family -- Juvenile Fiction. -- Parents; Humorous Stories. -- Juvenile Fiction; Board Books -- Fiction; Board books